Las marcas de lo institucional en el funcionamiento de las redes de apoyo - (:unkn) unknown (Universitat Autònoma de Barcelona, 2024)
Teachers are a key building-block of the educational process. In a limit situation that disrupted everyday life, such as that of the COVID-19 pandemic, how were teachers’ personal support networks put into motion to respond to their emerging work-relat...
Keywords: Redes de apoyo; Instituciones